Environmental Compliance Assessment of Wastewater and Solid Waste Management in Minh Tien Cooperatives Paper and Packaging Factory, Phu Lam Industrial Cluster, Tien Du Commune, Bac Ninh Province - Quang Tuan, Luu; Thi Viet Anh, Pham (VNU Journal of Science: Earth and Environmental Sciences, 2025)
With the increasingly strict legal requirements both in Vietnam and globally for industries like paper manufacturing, regular environmental assessment is essential to move toward sustainable development goals. This study focuses on assessing the compliance of Minh Tien Cooperatives paper and packaging factory, located in the Phu Lam Industrial Cluster (Tien Du commune, Bac Ninh Province), with environmental regulations related to wastewater and solid waste. Environmental monitoring data from 2023 - 2024 and related reports show that the factory’s wastewater overall meets national standards. However, at certain times, the levels of COD (Chemical Oxygen Demand) and BOD 5 (Biological Oxygen Demand) exceeded the limits set in QCVN 12-MT:2015/BTNMT and QCVN 40:2011/BTNMT. The amount of general solid waste generated was higher than what was reported. In addition, the waste separation and storage were not fully implemented as per regulation. Although the factory submitted its environmental reports on time, some important details were missing. Based on these findings, some suggestions have been proposed to help the factory improve its environmental performance.